A STUDY OF TRADITIONAL FINANCE AND BEHAVIOURAL FINANCE: RATIONALITY TO IRRATIONALITY - Sharma, Surbhi; Sharma, Dr. Saurabh (The journal of contemporary issues in business and government, 2022)
Purpose of this research to do detailed study in the area of traditional finance and behavioural finance. This paper is focused on understanding the reason behind investment decision making and how financial theories like EMH are ineffective to understand market variances and human behaviour. There are two divisions to analyses the review and discussion of literature as follows development phase of EMH and disappointment of EMH, which introduce the area of behavioural finance. Efficient market theory is first introducing by Eugene Fama in the year 1960s. After that EMH model turn into most significant financial model in the area of enlightening the stock market behaviour, it is considering as the best model to predict stock market in 1970s. Current research introduce how behavioural finance evolve from the major drawback assumption of rationality in domain finance. This research is beneficiary or academician, stock market investor as well as financial market managers so they can understand stock market behaviour.